Optimización de la extracción por solventes de compuesto de la corteza y hojas de Spondias mombin L. (ubos) y evaluación de la capacidad antioxidante - Paima Roque, Mikol Kitty (2022)
Spondias mombin L., is a plant dispersed throughout the tropical regions of South America, Africa and Asia, where the leaves and bark are used in preparations for neuropsychiatric disorders due to their metabolite content. The present study was designed to describe the optimal experimental conditions, using the response surface methodology to maximize the extraction efficiency of bark and leaves of Spondias mombin L., based on an experimental design to validate an appropriate method to simultaneously quantify the yield. extraction and total phenol compounds. The main variables were evaluated, which were the extraction time and solvent ratio, the extraction of the bark and leaves through the composition that shows 66.46±0.86% humidity in the bark and 70.55±0.08% humidity in the leaves, resulting in significant difference (p<0.05) and 3.87±0.09% of ash in the bark and 3.20±0.67 in respectively. Likewise, the content of total phenols and the antioxidant capacity of the bark and leaf extract were determined by the DPPH? and ABTS•+ methods. The optimal conditions for the yield of the extracts equivalent to 12.01% were obtained in 5 days, the highest concentration of ethanol was for the bark, and when working with the leaves the highest extraction yield equivalent to 3.1% was reached in the range 6 at 7 days and 0.3 to 0.6 ratio of solvent to ethanol.